Effects of the Empowerment Program in Care Giver on Health literacy and Caring Behavior for Dependent Older Adults in the Community - Dakam, Jaranya; Jantacumma, Napaphen; Wongsawang, Nongnuch (Journal of The Royal Thai Army Nurses, 2025)
This quasi-experimental research aimed to compare the health literacy and caregiving behaviors of caregivers for dependent elderly individuals before and after participating in a caregiver empowerment program, as well as to compare post-intervention outcomes between the experimental and comparison groups. The research employed a quasi-experimental design. Participants included 56 caregivers of dependent older adults, divided into two groups of 28 through simple random sampling. The experimental group comprised caregivers from Non Tan subdistrict, while the comparison group consisted of caregivers from Kut Kwang subdistrict. The intervention was a caregiver empowerment program, conducted over 12 weeks. Data collection tools included questionnaires assessing (1) health literacy and (2) caregiving behaviors. Data were analyzed using descriptive statistics and inferential statistics, including the Mann-Whitney U test and Wilcoxon signed-rank test. The results showed that: 1) After the program, the experimental group demonstrated significantly improved health literacy and caregiving behaviors compared to pre-intervention levels (p < .05). 2) After the program, The experimental group outperformed the comparison group in both health literacy and caregiving behaviors (p < .05). Therefore, caregiver empowerment effectively enhances health literacy and promotes caregiving behaviors for dependent elderly individuals.